The Scribes of Flateyjarbók, GKS 1005 fol. A Study in Scribal Practice in 14th-Century Iceland - Pagani, Roberto, 1990- (2015)
This study is a comparative analysis of the language and script of the two scribes of Flateyjarbók, GKS 1005 fol., dated to c1387–1394. The importance of this manuscript for the history of the Icelandic language and script lies in the internal evidence concerning its writing, which does not rely on the language or the script. In fact, an indication of the time of writing is found in the text, and the two scribes who carried out the work are named: Jón Þórðarson and Magnús Þórhallsson. A study of the language and script of Flateyjarbók and a comparative analysis of the scribal practice of the two individuals who wrote it can thus shed light on the status of the Icelandic language and script at the time and provide valuable comparative material for the study of other manuscripts that cannot be dated independently. Furthermore, the copious amount of text contained in this monumental collection contributes to making statistical estimates more effective. Both linguistic and palaeographic data has been extrapolated from the manuscript and analysed. The linguistic analysis shows a degree of variation between the two. Though this is not equally conclusive for all the features analysed, the results appear to suggest that the language of the first scribe is more innovative. From the orthographic and palaeographic analysis, it emerges that the script of Jón Þórðarson is on the one hand less pronouncedly angular and uniform, but on the other also less cursive than that of Magnús Þórhallsson. From the analysis of the data gathered, it seems reasonable to conclude that it is the language of Jón that shows a more innovative character, and that of Magnús which appears to be more conservative.